Suplementação de fitase em dietas com redução nos níveis nutricionais para codornas de corte e postura - Melo, Lucas Nunes de (2019)
To evaluate the effects of phytase supplementation was performed two experiments with quails and eat and laying. The objective was to evaluate the effects of phytase supplementation in the diet with reduced levels of available phosphorus, calcium, amino acids digestible and metabolizable energy for quails in performance parameters, carcass traits, intestinal morphology and bone strength. 680 European quails (Coturnix coturnix coturnix) from 1 to 45 days-old, distributed in a completely randomized design with five treatments and eight replicates of 17 birds each. Treatments consisted of a diet with reduced 0.150 and 0.165 percentage points available phosphorus and calcium, respectively, in 10% digestible amino acid levels (methionine + cystine lysine and threonine) and reduction of 50 kcal / kg metabolizable energy. On this diet were supplemented 0; 500; 1,000; 1,500 and 2,000 FTU / kg of phytase. Phytase influenced weight gain, feed conversion and carcass weight (P<0.05). With the exception of ileus villus height, intestinal morphology of all variables were affected (P<0.05) by the enzyme, as well as the tibia resistance. It is recommended tophytase supplementation level of 1,000 FTU / kg feed with a reduction in the levels of available phosphorus, calcium, amino acids digestible and metabolizable energy for quails. For the laying experiment aimed to evaluate the effects of phytase supplementation in diets with reduction in levels of available phosphorus, calcium, amino acids digestible and metabolizable energy for Japanese quails in laying phase under the parameters of performance and egg quality. 280 Japanese quails (Coturnix coturnix japonica) 115-325 days-old, distributed in a completely randomized design with five treatments and eight replicates of 7 birds each. Treatments consisted of a diet with a reduction of 0.150 and 0.165 percentage points in available phosphorus and calcium, respectively, In 10% digestible amino acid levels (methionine + cystine, lysine and threonine) and reduction of 50 kcal / kg metabolizable energy. On this diet were supplemented 0; 500; 1,000; 1,500 and 2,000 FTU / kg of phytase. The experiment was divided into two phases: 115-220 days (Posture I) and days 220-325 (Posture II), divided into five periods of 21 days each. Phytase influenced the mass conversion and dozen eggs instance phases I and II; and egg production, feed intake and egg mass in phase II posture (P <0.05). To egg quality only Haugh unit was influenced (P <0.05) by the phytase in both phases.The phytase supplementation level of 1500 FTU / kg feed with a reduction in the levels of available phosphorus, calcium, amino acids digestible and metabolizable energy is sufficient to ensure improved performance of Japanese quails in the laying phase.